Identification of potential novel roles for Hsp70/Hsp90 organising protein (Hop) using proteomic analysis in human cells - Wingate, Ianthe (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2016)
Expected release date-May 2018
Keywords: Uncatalogued